SOLUTION
Given the question in the image, the following are the solution steps to get the answer
Step 1: Define antiderivative
Antiderivative of a function is nothing but integral with respect to x
![F(x)=\int f(x)dx](https://img.qammunity.org/2023/formulas/mathematics/college/3elocfs5lyma853z09frjgw136j4xephhp.png)
Step 2: Find the antiderivative of the given function in the question
![\begin{gathered} f(x)=12x-9 \\ F(x)=\int (12x-9)dx \\ \text{Providing integral to each term, we have} \\ F(x)=\int 12xdx-\int 9dx \\ F(x)=12\int xdx-9\int x^0dx---(1) \\ we\text{ know that} \\ \int x^ndx=\frac{x^{^(n+1)^{}}}{n+1},n\\e1 \\ F(x)=12*(x^(1+1))/(1+1)-9*(x^(0+1))/(0+1)+c \\ F(x)=12*(x^2)/(2)-9*(x)/(1)+c \\ F(x)=6x^2-9x+c----(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8jun6nmegkcy4ajtg84ezk16j8iooobs7g.png)
Step 3: we find the value of c in front of the integration formula
![\begin{gathered} \text{Given that F(1)=7} \\ 6(1)^3-9(1)+c=7 \\ 6-9+c=7 \\ c=7-6+9 \\ c=10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qkbuo1ib9es5sty3ai0htmcdbw0sf8b46w.png)
Step 4: We write the final result for F(x)
![\begin{gathered} \text{Hence, we have:} \\ F(x)=6x^2-9x+10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/txnmxipt8ya7oj3slfkkryrjkh6vto0fdh.png)
Hence, the final result for F(x) is given as:
![F(x)=6x^2-9x+10](https://img.qammunity.org/2023/formulas/mathematics/college/cvoca8x7t8phk0wecqfcwk7c9v76mvmim4.png)